ETIKA ADMINISTRASI DAN TATA KELOLA PENDIDIKAN YANG AKUNTABEL - Rameyza Elya Balqis; Haris Riadi; Umi Wulandari (Jurnal Manajemen Pendidikan, 2026)
Education is a strategic sector that plays a vital role in improving the quality of human resources and the progress of a nation. Achieving quality education requires accountable educational governance supported by the implementation of strong administrative ethics. This study aims to analyze the role of administrative ethics in building accountable educational governance and examine the relationship between administrative ethical values ​​and improving the quality of educational institution management. This study uses a library research method by reviewing various literature sources such as books, scientific journals, and research results relevant to the topic of administrative ethics and educational governance. Data are analyzed descriptively and qualitatively to obtain a comprehensive understanding of the concept, role, and implementation of administrative ethics in education. The results of the study indicate that administrative ethics plays a role in increasing transparency, professionalism, responsibility, and public trust in educational institutions. Accountable educational governance is influenced by ethical leadership, a transparent administrative system, human resource competence, and clear regulations. Thus, the consistent application of administrative ethics can support the realization of quality, integrity, and sustainable education.